Association of obesity-related anthropometric indicators with chronic constipation and diarrhea among U.S. adults: a cross-sectional study - Ning, Yu; Hu, Xiaoting; Li, Laifu; Zhuang, Yan; Dai, Fei (Frontiers in Nutrition, 2025)
AimPrior studies have linked obesity indicators to constipation/diarrhea, but multi-measure comparisons remain limited. We analyzed these associations in U.S. adults.MethodsThis cross-sectional study utilized data from three cycles (2005–2010) of the National Health and Nutrition Examination Survey (NHANES). The final analysis included 13,105 participants after excluding those aged < 20 years or with missing data for any study variables. Bowel habits were categorized using the Bristol Stool Form Scale (BSFS). Multiple analytical approaches were employed: descriptive statistics, weighted multivariable logistic regression, weighted restricted cubic spline (RCS) analysis, subgroup analyses, and sensitivity analysis. We evaluated the diagnostic performance of various anthropometric indices—waist circumference (WC), body mass index (BMI), relative fat mass (RFM), body roundness index (BRI), weight-adjusted waist index (WWI), waist-to-height ratio (WHtR), and a body shape index (ABSI)—for chronic diarrhea and constipation using receiver operating characteristic (ROC) curve analysis and the area under the curve (AUC).ResultsWeighted multivariable logistic regression revealed significant positive associations between seven obesity indicators and diarrhea (all P < 0.05), with the highest odds ratios (ORs) observed in the top quartiles for WWI (OR = 1.937, 95% CI = 1.516–2.474, P < 0.001) and RFM (OR = 1.870, 95% CI = 1.254–2.790, P = 0.003). Meanwhile, RFM, BRI, WC, BMI, and WHtR showed significant inverse associations with constipation (P < 0.05), with the lowest ORs observed for the top quartiles of BMI (OR = 0.530, 95% CI = 0.408–0.689, P < 0.001) and RFM (OR = 0.599, 95% CI = 0.409–0.879, P = 0.011). By contrast, the top ABSI quartile exhibited a positive association with constipation (OR = 1.262, 95% CI = 1.014–1.571, P = 0.038). ROC analysis indicated RFM as the most discriminative indicator for constipation (AUC = 0.577) and WWI for diarrhea (AUC = 0.614), respectively, among tested indices. RCS analysis demonstrated an inverse J-shaped relationship between RFM and constipation and a linear positive association between WWI and diarrhea. Subgroup analyses further validated the robust associations of RFM and WWI with intestinal disorders across strata of age, sex, race, smoking, drinking, sleep disturbances, diabetes, and depression. Sensitivity analyses yielded consistent results, supporting the stability of these findings.ConclusionsThe seven indicators are useful indicators for assessing intestinal disorders in U.S. adults, with RFM and WWI demonstrating the highest discriminative ability for constipation and diarrhea, respectively.